2012
DOI: 10.1371/journal.ppat.1002502
|View full text |Cite
|
Sign up to set email alerts
|

HCMV Targets the Metabolic Stress Response through Activation of AMPK Whose Activity Is Important for Viral Replication

Abstract: Human Cytomegalovirus (HCMV) infection induces several metabolic activities that have been found to be important for viral replication. The cellular AMP-activated protein kinase (AMPK) is a metabolic stress response kinase that regulates both energy-producing catabolic processes and energy-consuming anabolic processes. Here we explore the role AMPK plays in generating an environment conducive to HCMV replication. We find that HCMV infection induces AMPK activity, resulting in the phosphorylation and increased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
111
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(113 citation statements)
references
References 44 publications
2
111
0
Order By: Relevance
“…Recent studies have shown that eIF4F is required for the translation of several host metabolic enzymes (27). As HCMV infection remodels host metabolism (20,(33)(34)(35)(36), perhaps the increased eIF4F abundance and activity in infected cells promotes the expression of metabolic enzymes needed for virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that eIF4F is required for the translation of several host metabolic enzymes (27). As HCMV infection remodels host metabolism (20,(33)(34)(35)(36), perhaps the increased eIF4F abundance and activity in infected cells promotes the expression of metabolic enzymes needed for virus replication.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it enables AMPK to be activated in response to acute energy insufficiency without concomitant mTORC1 inhibition. A distinct but related strategy operates in HCMV-infected cells whereby AMPK activation stimulates productive HCMV replication (7,9). Instead of the Us3 kinase, which is specific to alphaherpesviruses, HCMV encodes the TSC2 binding protein UL38 to antagonize TSC activity and stimulate mTORC1 (40).…”
Section: Discussionmentioning
confidence: 99%
“…Instead of the Us3 kinase, which is specific to alphaherpesviruses, HCMV encodes the TSC2 binding protein UL38 to antagonize TSC activity and stimulate mTORC1 (40). This precludes AMPK-mediated inhibition of mTORC1 while supporting AMPK-dependent metabolic changes conducive to virus reproduction (7,9). Compared to betaherpesviruses like HCMV, alphaherpesviruses have a very fast productive growth cycle that may not require AMPK activation.…”
Section: Discussionmentioning
confidence: 99%
“…Some viruses stimulate an increase in host intracellular glucose levels to increase the energy available for replication by affecting signal transduction pathways associated with sugar metabolism (39,40). Intracellular Salmonellae have been shown to relay on host intracellular glucose (41).…”
Section: Discussionmentioning
confidence: 99%